Individual differences in effectiveness of cochlear implants in children who are prelingually deaf: new process measures of performance. - Pisoni DB; Cleary M; Geers AE; Tobey EA (Volta Review)
The efficacy of cochlear implants in children who are deaf has been firmly established in the literature. However, the effectiveness of cochlear implants varies widely and is influenced by demographic and experiential factors. Several key findings suggest new directions for research on central auditory factors that underlie the effectiveness of cochlear implants. First, enormous individual differences have been observed in both adults and children on a wide range of audiological outcome measures. Some patients show large increases in speech perception scores after implantation, whereas others display only modest gains on standardized tests. Second, age of implantation and length of deafness affect all outcome measures. Children implanted at younger ages do better than children implanted at older ages, and children who have been deaf for shorter periods do better than children who have been deaf for longer periods. Third, communication mode affects outcome measures. Children from 'oral-only' environments do much better on standardized tests that assess phonological processing skills than children who use Total Communication. Fourth, at the present time there are no preimplant predictors of outcome performance in young children. The underlying perceptual, cognitive, and linguistic abilities and skills emerge after implantation and improve over time. Finally, there are no significant differences in audiological outcome measures among current implant devices or processing strategies. This finding suggests that the major source of variance in outcome measures lies in the neural and cognitive information processing operations that the user applies to the signal provided by the implant. Taken together, this overall pattern of results suggests that higher-level central processes such as perception, attention, learning, and memory may play important roles in explaining the large individual differences observed among users of cochlear implants. Investigations of the content and flow of information in the central nervous system and interactions between sensory input and stored knowledge may provide important new insights into the basis of individual differences. Knowledge about the underlying basis of individual differences may also help in developing new intervention strategies to improve the effectiveness of cochlear implants in children who show relatively poor development of oral/aural language skills.